2016
DOI: 10.1111/1475-6773.12544
|View full text |Cite
|
Sign up to set email alerts
|

Implications of Variation in the Relationships between Beneficiary Characteristics and Medicare Advantage CAHPS Measures

Abstract: Customized reporting may help consumers select the best Medicare Advantage plan, but policies should protect against unintended consequences.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 30 publications
0
10
0
Order By: Relevance
“… 11 , 12 For example, health organizations that use the Consumer Assessment of Healthcare Providers and Systems (CAHPS) survey to assess patient-reported satisfaction commonly adjust for a patient’s general and mental health status and educational level. 5 However, the association between race/ethnicity and patient satisfaction scores—and the consequent need to make statistical adjustments for patient race/ethnicity—remains uncertain. Many previous studies have examined differences in the patient satisfaction scores of black or African American and Hispanic patients relative to non-Hispanic white patients (hereafter simply referred to as white patients).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“… 11 , 12 For example, health organizations that use the Consumer Assessment of Healthcare Providers and Systems (CAHPS) survey to assess patient-reported satisfaction commonly adjust for a patient’s general and mental health status and educational level. 5 However, the association between race/ethnicity and patient satisfaction scores—and the consequent need to make statistical adjustments for patient race/ethnicity—remains uncertain. Many previous studies have examined differences in the patient satisfaction scores of black or African American and Hispanic patients relative to non-Hispanic white patients (hereafter simply referred to as white patients).…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] Furthermore, a growing body of literature has demonstrated that immutable, patient-level characteristics, such as age, overall health status, educational level, and race/ethnicity, serve as important determinants of patient-reported satisfaction. [4][5][6][7][8][9][10] To avoid possible measurement bias, health organizations adjust patient satisfaction scores for various characteristics, including age, sex, and health status. 11,12 For example, health organizations that use the Consumer Assessment of Healthcare Providers and Systems (CAHPS) survey to assess patient-reported satisfaction commonly adjust for a patient's general and mental health status and educational level.…”
Section: Introductionmentioning
confidence: 99%
“…Potential case-mix variables for analysis of the Field Trial data will be selected based on theoretical notions and empirical evidence. [35][36][37][38][39][40] Depending on the data analysis of the Field Trial, the case-mix adjustment in the analyses of the Main Survey data may be modified.…”
Section: Methodsmentioning
confidence: 99%
“…Case-mix variables are variables that may hamper a fair comparison of patient-reported indicators between countries or regions. Potential case-mix variables for analysis of the Field Trial data will be selected based on theoretical notions and empirical evidence 35–40. Depending on the data analysis of the Field Trial, the case-mix adjustment in the analyses of the Main Survey data may be modified.…”
Section: Methodsmentioning
confidence: 99%
“…Uniformity of relationship between the candidate case-mix adjustor and a patient experience measure over strata (case-mix model coefficients; (Elliott et al 2001;Zaslavsky et al 2000)). Analysis of the Medicare CAHPS data found evidence of variation in case-mix adjustment coefficients across plans, but its effect on comparative scores was minimal (Hatfield and Zaslavsky 2017).…”
Section: Selection Of Case-mix Adjustment Variablesmentioning
confidence: 98%